Positive electrode and secondary battery using them

By using a specific range of lithium composite oxide combinations in the positive electrode materials of the secondary battery, the problem of difficult balance of capacity and output characteristics is solved, and the battery performance improvement of high capacity and high output is achieved.

JP2025014965AActive Publication Date: 2025-01-30PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023117972
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30
Estimated Expiration
2043-07-20

AI Technical Summary

Technical Problem

The prior art is difficult to balance capacity and output characteristics in secondary batteries, and cannot achieve high levels of capacity and output performance at the same time.

Method used

Using a positive electrode material layer containing the first and second lithium composite oxides, the Li/Me molar ratio of the first lithium composite oxide is 0.90 to 0.97, the Li/Me molar ratio of the second lithium composite oxide is 1.10 to 1.20, and the grain diameter thereof is controlled within a specific range, in combination with appropriate preparation methods to form a layered structure.

Benefits of technology

The secondary battery has achieved significant improvements in high capacity and high output characteristics, and improved the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014965000001_ABST
    Figure 2025014965000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode which can apply a capacity characteristic and an output characteristic to a secondary battery at a high level.SOLUTION: A positive electrode disclosed here, comprises: a positive electrode collector; and a positive electrode active material layer supported by the positive electrode collector. The positive electrode active material layer contains a first lithium composite oxide having a layer-shaped structure and a second lithium composite oxide having a layer-shaped structure. In the first lithium composite oxide, a mole ratio of Li to a metal other than Li is 0.90 to 0.97. In the second lithium composite oxide, a mole ratio of Li to the metal other than Li is 1.10 to 1.20. A crystallite diameter of a (104) surface of the first lithium composite oxide is 400Å to 600Å. The crystallite diameter of the (104) surface of the second lithium composite oxide is larger than the crystallite diameter of the (104) surface of the first lithium composite oxide.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode. The present invention also relates to a secondary battery using the positive electrode. [Background technology]

[0002] 2. Description of the Related Art In recent years, secondary batteries such as lithium-ion secondary batteries have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), among others.

[0003] A positive electrode active material is generally used for a positive electrode used in a secondary battery such as a lithium ion secondary battery. Lithium composite oxide is often used as the positive electrode active material. Patent Document 1 discloses that a lithium composite oxide having a Li / Me ratio of 1 or less and a lithium-excess lithium composite oxide (i.e., a lithium composite oxide having a Li / Me ratio exceeding 1) are used in combination as a positive electrode active material, and the crystallite diameter of the lithium composite oxide having a Li / Me ratio of 1 or less is set to 180 nm or more (1800 Å or more), thereby improving the output characteristics, capacity characteristics, etc. of a secondary battery. The Li / Me ratio of the lithium composite oxide is the molar ratio of Li to a metal other than Li (Me). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2021-518049 Summary of the Invention [Problem to be solved by the invention]

[0005] However, as a result of intensive research by the present inventors, it has been newly discovered that the above-mentioned conventional technology has a problem in that it is not possible to achieve both high levels of capacitance characteristics and output characteristics.

[0006] Therefore, an object of the present invention is to provide a positive electrode that can impart high levels of both capacity characteristics and output characteristics to a secondary battery. [Means for solving the problem]

[0007] The positive electrode disclosed herein includes a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector. The positive electrode active material layer contains a first lithium composite oxide having a layered structure and a second lithium composite oxide having a layered structure. In the first lithium composite oxide, the molar ratio of Li to metals other than Li is 0.90 to 0.97. In the second lithium composite oxide, the molar ratio of Li to metals other than Li is 1.10 to 1.20. The crystallite diameter of the (104) plane of the first lithium composite oxide is 400 Å to 600 Å. The crystallite diameter of the (104) plane of the second lithium composite oxide is larger than the crystallite diameter of the (104) plane of the first lithium composite oxide.

[0008] According to such a configuration, it is possible to provide a positive electrode that can impart high levels of both capacity characteristics and output characteristics to a secondary battery.

[0009] From another aspect, a secondary battery disclosed herein includes the above-mentioned positive electrode, a negative electrode, and an electrolyte. With this configuration, it is possible to provide a secondary battery having both high capacity characteristics and high output characteristics. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a positive electrode according to one embodiment of the present invention. [Diagram 2] 1 is a cross-sectional view showing a schematic internal structure of a lithium-ion secondary battery according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic exploded view showing the configuration of a wound electrode body of a lithium ion secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Matters not mentioned in this specification but necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. In addition, in the following drawings, members and parts having the same function are described with the same reference numerals. Furthermore, the dimensional relationships (length, width, thickness, etc.) in each drawing do not reflect the actual dimensional relationships. In addition, the numerical range expressed as "A to B" in this specification includes A and B.

[0012] In this specification, the term "secondary battery" refers to an electricity storage device that can be repeatedly charged and discharged. In addition, in this specification, the term "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as a charge carrier and realizes charging and discharging by the transfer of charge associated with the lithium ions between the positive and negative electrodes.

[0013] Hereinafter, the present invention will be described in detail using a positive electrode used in a lithium ion secondary battery as an example, but it is not intended to limit the present invention to the embodiment described therein. Fig. 1 is a schematic cross-sectional view of the positive electrode according to this embodiment taken along the thickness direction and the width direction.

[0014] As shown in the figure, the positive electrode 50 includes a positive electrode current collector 52 and a positive electrode active material layer 54 supported by the positive electrode current collector 52. In the illustrated example, the positive electrode active material layer 54 is provided on both sides of the positive electrode current collector 52. However, the positive electrode active material layer 54 may be provided on one side of the positive electrode current collector 52. Preferably, the positive electrode active material layer 54 is provided on both sides of the positive electrode current collector 52.

[0015] As shown in the illustrated example, a positive electrode active material layer non-forming portion 52a where no positive electrode active material layer 54 is provided may be provided at one end in the width direction of the positive electrode 50. In the positive electrode active material layer non-forming portion 52a, the positive electrode current collector 52 is exposed, and the positive electrode active material layer non-forming portion 52a can function as a current collector. However, the configuration for collecting current from the positive electrode 50 is not limited to this.

[0016] A known positive electrode current collector used in lithium ion secondary batteries may be used as the positive electrode current collector 52, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., aluminum, nickel, titanium, stainless steel, etc.). As the positive electrode current collector 52, aluminum foil is preferred.

[0017] The dimensions of the positive electrode current collector 52 are not particularly limited and may be appropriately determined depending on the battery design. When an aluminum foil is used as the positive electrode current collector 52, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.

[0018] The positive electrode active material layer 54 contains a positive electrode active material. In this embodiment, a first lithium composite oxide having a layered structure and a second lithium composite oxide having a layered structure are used in combination as the positive electrode active material. Therefore, the positive electrode active material layer contains at least the first lithium composite oxide and the second lithium composite oxide. In the following description, when the term "lithium composite oxide" is used, the description basically refers to matters that apply to both the first lithium composite oxide and the second lithium composite oxide.

[0019] Examples of types of lithium composite oxides having a layered structure include lithium nickel composite oxides, lithium cobalt composite oxides, lithium manganese composite oxides, lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium iron nickel manganese composite oxides.

[0020] In this specification, the term "lithium nickel cobalt manganese composite oxide" includes oxides containing Li, Ni, Co, Mn, and O as constituent elements, as well as oxides containing one or more additional elements other than those. Examples of such additional elements include transition metal elements and typical metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn. The additional element may be a semimetal element such as B, C, Si, or P, or a nonmetal element such as S, F, Cl, Br, or I. This also applies to the above-mentioned lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide.

[0021] The first lithium composite oxide and the second lithium composite oxide may be the same type of lithium composite oxide, or may be different types of lithium composite oxides.

[0022] When different types of lithium composite oxides are used, it is easy to distinguish between the first lithium composite oxide and the second lithium composite oxide.

[0023] When the same type of lithium composite oxide is used, it is easy to adjust the characteristics of the lithium ion secondary battery 100. When the same type of lithium composite oxide is used, it is preferable that both the first lithium composite oxide and the second lithium composite oxide are lithium nickel cobalt manganese-based composite oxide or lithium nickel cobalt aluminum-based composite oxide, and it is more preferable that both are lithium nickel cobalt manganese-based composite oxide. In this specification, the lithium composite oxide is the same type as the lithium composite oxide, and the constituent elements contained in the lithium composite oxide are the same. Therefore, for example, if both the first lithium composite oxide and the second lithium composite oxide are lithium nickel cobalt manganese-based composite oxide, they are the same type of lithium composite oxide even if the element ratio of the constituent elements is different between the first lithium composite oxide and the second lithium composite oxide.

[0024] The positive electrode active material may be composed only of the first lithium composite oxide and the second lithium composite oxide. However, the positive electrode active material layer 54 may contain a positive electrode active material other than the first lithium composite oxide and the second lithium composite oxide within a range that does not significantly impair the effects of the present invention (for example, 10 mass % or less, 5 mass % or less, or 1 mass % or less with respect to the total mass of the positive electrode active material).

[0025] In the first lithium composite oxide, the molar ratio of Li to metals other than Li (Me) (hereinafter also referred to as "Li / Me ratio") is 0.90 to 0.97, while in the second lithium composite oxide, the molar ratio of Li to metals other than Li (Me) (Li / Me ratio) is 1.10 to 1.20.

[0026] Furthermore, the crystallite diameter of the (104) plane of the first lithium composite oxide is 400 Å to 600 Å. In addition, the crystallite diameter of the (104) plane of the second lithium composite oxide is larger than the crystallite diameter of the (104) plane of the first lithium composite oxide.

[0027] In this way, by setting the Li / Me ratio of the two types of lithium composite oxides within the above range and the crystallite size of the (104) plane within the above range, the output characteristics and capacity characteristics of the lithium ion secondary battery 100 using the positive electrode 50 can be improved. The reason for this is believed to be as follows. By balancing the Li / Me ratio and limiting the crystallite size, when lithiation occurs in the lithium composite oxide (particularly the first lithium composite oxide), the formation of an excess resistance layer (Li2CO3 or LiOH) on the surface of the lithium composite oxide is suppressed, and rearrangement of the crystal structure occurs. These contribute to the improvement of the output characteristics and capacity characteristics.

[0028] Specifically, when the Li / Me ratio in the first lithium composite oxide is outside the range of 0.90 to 0.97, the capacity characteristics are insufficient. When the Li / Me ratio in the second lithium composite oxide is outside the range of 1.10 to 1.20, the capacity characteristics are also insufficient. From the viewpoint of increasing the capacity of the lithium ion secondary battery 100, the Li / Me ratio in the second lithium composite oxide is preferably 1.10 to 1.15, and more preferably 1.10 to 1.12.

[0029] When the crystallite diameter of the (104) plane of the first lithium composite oxide is outside the range of 400 Å to 600 Å, the output characteristics become insufficient. The crystallite diameter of the (104) plane of the first lithium composite oxide is preferably 500 Å to 600 Å, more preferably 550 Å to 600 Å, and further preferably 580 Å to 600 Å.

[0030] If the crystallite diameter of the (104) plane of the second lithium composite oxide is equal to or smaller than that of the (104) plane of the first lithium composite oxide, the output characteristics will be insufficient. The crystallite diameter of the (104) plane of the second lithium composite oxide is preferably 50 Å or more larger than that of the (104) plane of the first lithium composite oxide, more preferably 100 Å or more larger, even more preferably 150 Å or more larger, and particularly preferably 200 Å or more larger. The crystallite diameter of the (104) plane of the second lithium composite oxide is preferably 500 Å to 900 Å, more preferably 600 Å to 800 Å.

[0031] The Li / Me ratio and crystallite size of the lithium composite oxide can be adjusted according to a known method. For example, generally, lithium composite oxide is produced by mixing a precursor containing a metal element (Me) other than Li (e.g., hydroxide containing Me, carbonate containing Me, etc.) with a Li source compound (e.g., lithium hydroxide, lithium carbonate, lithium chloride, etc.) and calcining it. Here, the Li / Me ratio can be controlled by adjusting the mixing ratio of the precursor and the Li source compound. In addition, the crystallite size can be controlled by adjusting the calcination conditions. In particular, when the calcination temperature is increased, the crystallite size tends to become larger.

[0032] In addition, in a used lithium ion secondary battery, the Li / Me ratio of the lithium composite oxide may become smaller due to the desorption of Li. In addition, the crystallites may be destroyed and become smaller due to the expansion / contraction of the lithium composite oxide during the charge / discharge cycle. For this reason, in a used lithium ion secondary battery, a layered lithium composite oxide may be produced in which the Li / Me ratio is in the range of 0.90 to 0.97 and the crystallite diameter of the (104) plane is in the range of 400 Å to 600 Å.

[0033] Therefore, in this embodiment, a lithium composite oxide having a layered structure recovered from a used lithium ion secondary battery can be used as the first lithium composite oxide. This is advantageous from the viewpoint of reducing the environmental load. The lithium composite oxide can be recovered from a used lithium ion secondary battery by a known method. For example, a used lithium ion secondary battery is disassembled to remove the positive electrode, the positive electrode active material layer is peeled off from the positive electrode current collector, the binder is removed using a solvent, and the lithium composite oxide and the conductive material are separated by classification or the like to obtain a lithium composite oxide. On the other hand, the second lithium composite oxide may be a lithium composite oxide that has not been recycled.

[0034] The crystallite size of the (104) plane of the lithium composite oxide can be determined by performing X-ray diffraction (XRD) measurement on the powder of the lithium composite oxide. Specifically, the X-ray diffraction pattern is measured using a known X-ray diffraction (XRD) device, and the crystallite size can be calculated using the half-width (FWHM) of the diffraction peak (2θ=44±1°) assigned to the (004) plane, the 2θ value, and the Scherrer formula. When the positive electrode active material is already contained in the positive electrode, only the positive electrode active material may be isolated according to a known method and used as the measurement sample.

[0035] When the first lithium composite oxide is a lithium nickel cobalt manganese-based composite oxide, the first lithium composite oxide has a composition represented by, for example, the following formula (I). Li x1 Ni y1 Co z1 Mn (1-y1-z1) M1 α1 O 2-β1 Q1 β1 (I)

[0036] In formula (I), x1, y1, z1, α1, and β1 respectively satisfy 0.90 ≦ x1 ≦ 0.97, 0 < y1 ≦ 0.40, 0 < z1 ≦ 0.40, 0 ≦ α1 ≦ 0.10, and 0 ≦ β1 ≦ 0.5. M1 is at least one element selected from the group consisting of Zr, Mo, W, Mg, Ca, Na, Fe, Cr, Zn, Sn, B, and Al. Q1 is at least one element selected from the group consisting of F, Cl, and Br.

[0037] y1 preferably satisfies 0.05 ≦ y1 ≦ 0.40. z1 preferably satisfies 0.05 ≦ z1 ≦ 0.40. α1 preferably satisfies 0 ≦ α1 ≦ 0.05, more preferably 0 ≦ α1 ≦ 0.03. β1 preferably satisfies 0 ≦ β1 ≦ 0.1, more preferably 0.

[0038] When the second lithium composite oxide is a lithium nickel cobalt manganese-based composite oxide, the second lithium composite oxide has a composition represented by, for example, the following formula (II). Li x2 Ni y2 Co z2 Mn (1-y2-z2) M2 α2 O 2-β2 Q2 β2 (II)

[0039] In formula (II), x2, y2, z2, α2, and β2 satisfy 1.10 ≦ x ≦ 1.20, 0 < y2 ≦ 0.40, 0 < z2 ≦ 0.40, 0 ≦ α2 ≦ 0.10, and 0 ≦ β2 ≦ 0.5, respectively. M2 is at least one element selected from the group consisting of Zr, Mo, W, Mg, Ca, Na, Fe, Cr, Zn, Sn, B, and Al. Q2 is at least one element selected from the group consisting of F, Cl, and Br.

[0040] x2 preferably satisfies 1.10 ≦ x2 ≦ 1.15, and more preferably satisfies 1.10 ≦ x2 ≦ 1.12. y2 preferably satisfies 0.05 ≦ y2 ≦ 0.40. z2 preferably satisfies 0.05 ≦ z2 ≦ 0.40. α2 preferably satisfies 0 ≦ α2 ≦ 0.05, and more preferably α2 = 0. β2 preferably satisfies 0 ≦ β2 ≦ 0.1, and more preferably β2 = 0.

[0041] The compositions of the first lithium composite oxide and the second lithium composite oxide may be the same or different even if the compositions other than the Li / Me ratio are the same.

[0042] When the compositions of the first lithium composite oxide and the second lithium composite oxide are different, it is easy to distinguish between the first lithium composite oxide and the second lithium composite oxide.

[0043] When the compositions of the first lithium composite oxide and the second lithium composite oxide other than the Li / Me ratio are the same, it is easy to adjust the characteristics of the lithium-ion secondary battery 100. In this case, for example, in the above formulas (I) and (II), x1 and x2 are different, but y1 = y2, z1 = z2, α1 = α2, β1 = β2, M1 = M2, and Q1 = Q2.

[0044] The average particle diameter (D50) of the first lithium composite oxide and the second lithium composite oxide is not particularly limited and is, for example, 0.05 μm to 25 μm. The average particle diameter (D50) of the first lithium composite oxide is preferably 1 μm to 15 μm, more preferably 2 μm to 12 μm, and further preferably 3 μm to 8 μm. When the average particle diameter (D50) of the first lithium composite oxide is 3 μm to 8 μm, the output characteristics of the lithium ion secondary battery are particularly improved. The average particle diameter (D50) of the second lithium composite oxide is preferably 1 μm to 15 μm, and more preferably 2 μm to 12 μm.

[0045] In this specification, the term "average particle size (D50)" refers to a particle size corresponding to a cumulative frequency of 50 volume % from the fine particle side having a small particle size in a volume-based particle size distribution based on a laser diffraction / scattering method. Therefore, the average particle size (D50) can be determined using a known laser diffraction / scattering type particle size distribution measuring device or the like.

[0046] The mixing ratio of the first lithium composite oxide to the second lithium composite oxide is not particularly limited, and the mass ratio of the first lithium composite oxide to the second lithium composite oxide is, for example, 5:95 to 95:5, preferably 10:90 to 90:10, more preferably 30:70 to 70:30, and further preferably 40:60 to 60:40.

[0047] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, but is preferably 87 mass% or more, more preferably 90 mass% or more, and even more preferably 96 mass% or more.

[0048] The positive electrode active material layer 54 may contain components other than the positive electrode active material, such as trilithium phosphate, a conductive material, a binder, etc. As the conductive material, for example, carbon black such as acetylene black (AB), carbon nanotubes (CNT), and other carbon materials (e.g., graphite, etc.) can be suitably used. As the binder, for example, polyvinylidene fluoride (PVdF) can be used. Furthermore, when CNT is used as the conductive material, the positive electrode active material layer 54 may contain a dispersant for CNT.

[0049] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, but is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 85 mass% or more and 99 mass% or less. The content of the trilithium phosphate in the positive electrode active material layer 54 is not particularly limited, but is preferably 0.1 mass% or more and 15 mass% or less, and more preferably 0.2 mass% or more and 10 mass% or less. The content of the conductive material in the positive electrode active material layer 54 is not particularly limited, but is preferably 0.1 mass% or more and 20 mass% or less, and more preferably 0.3 mass% or more and 15 mass% or less. The content of the binder in the positive electrode active material layer 54 is not particularly limited, but is preferably 0.4 mass% or more and 15 mass% or less, and more preferably 0.5 mass% or more and 10 mass% or less.

[0050] The thickness of the positive electrode active material layer 54 per side is not particularly limited, but is usually 10 μm or more, and preferably 20 μm or more. On the other hand, the thickness is usually 300 μm or less, and preferably 200 μm or less.

[0051] In the positive electrode 50, the positive electrode active material layer non-forming portion 52a may be provided with an insulating protective layer (not shown) containing insulating particles (e.g., ceramic particles) at a position adjacent to the positive electrode active material layer 54. This protective layer can prevent a short circuit between the positive electrode active material layer non-forming portion 52a and the negative electrode.

[0052] The positive electrode 50 according to this embodiment can be produced by preparing a positive electrode slurry containing a positive electrode active material, optional components (e.g., a binder, a conductive material, etc.), and a solvent (dispersion medium), applying the slurry onto the positive electrode current collector 52, drying the slurry, and then pressing the slurry as necessary.

[0053] The positive electrode 50 according to this embodiment can impart high levels of both capacity characteristics and output characteristics to a secondary battery.

[0054] From another aspect, the secondary battery according to this embodiment includes a positive electrode, a negative electrode, and an electrolyte, and the positive electrode is the positive electrode according to this embodiment described above.

[0055] Hereinafter, the secondary battery according to the present embodiment will be described in detail using a flat rectangular lithium ion secondary battery having a flat wound electrode body and a flat battery case as an example. However, the secondary battery according to the present embodiment is not limited to the example described below.

[0056] The lithium ion secondary battery 100 shown in FIG. 2 is a sealed battery constructed by housing a flat wound electrode body 20 and a nonaqueous electrolyte 80 in a flat rectangular battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. The battery case 30 is also provided with an injection port (not shown) for injecting the nonaqueous electrolyte 80. The positive electrode terminal 42 is electrically connected to the positive electrode current collector plate 42a. The negative electrode terminal 44 is electrically connected to the negative electrode current collector plate 44a. The material of the battery case 30 is, for example, a lightweight metal material with good thermal conductivity, such as aluminum. Note that FIG. 2 does not accurately represent the amount of the nonaqueous electrolyte 80.

[0057] As shown in Figs. 2 and 3, the wound electrode body 20 has a configuration in which a positive electrode sheet 50 and a negative electrode sheet 60 are overlapped with two long separator sheets 70 interposed therebetween and wound in the longitudinal direction.

[0058] The positive electrode sheet 50 used is the positive electrode 50 according to the present embodiment described above. The positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides here) of a long positive electrode current collector 52. The negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (both sides here) of a long negative electrode current collector 62.

[0059] The positive electrode 50 has a positive electrode active material layer non-forming portion 52a where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed. The negative electrode 60 has a negative electrode active material layer non-forming portion 62a where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed. The positive electrode active material layer non-forming portion 52a and the negative electrode active material layer non-forming portion 62a are formed so as to protrude outward from both ends in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction) of the wound electrode body 20. The positive electrode active material layer non-forming portion 52a and the negative electrode active material layer non-forming portion 62a are joined to the positive electrode current collector 42a and the negative electrode current collector 44a, respectively.

[0060] The negative electrode current collector 62 constituting the negative electrode sheet 60 may be a known negative electrode current collector used in lithium ion secondary batteries, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., copper, nickel, titanium, stainless steel, etc.). Copper foil is preferable as the negative electrode current collector 62.

[0061] The dimensions of the negative electrode current collector 62 are not particularly limited and may be appropriately determined depending on the battery design. When a copper foil is used as the negative electrode current collector 62, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.

[0062] The negative electrode active material layer 64 contains a negative electrode active material. Examples of the negative electrode active material include carbon materials such as graphite, hard carbon, and soft carbon; Si; and composite materials of Si and carbon. The graphite may be natural graphite or artificial graphite, or may be amorphous carbon-coated graphite in which graphite is coated with an amorphous carbon material.

[0063] The average particle size (D50) of the negative electrode active material is not particularly limited, but is, for example, 0.1 μm or more and 50 μm or less, preferably 1 μm or more and 25 μm or less, and more preferably 5 μm or more and 20 μm or less.

[0064] The negative electrode active material layer 64 may contain components other than the active material, such as a binder, a thickener, etc. As the binder, for example, styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), etc. may be used. As the thickener, for example, carboxymethyl cellulose (CMC), etc. may be used.

[0065] The content of the negative electrode active material in the negative electrode active material layer 64 is preferably 90% by mass or more, and more preferably 95% by mass or more and 99% by mass or less. The content of the binder in the negative electrode active material layer 64 is preferably 0.1% by mass or more and 8% by mass or less, and more preferably 0.5% by mass or more and 3% by mass or less. The content of the thickener in the negative electrode active material layer 64 is preferably 0.3% by mass or more and 3% by mass or less, and more preferably 0.5% by mass or more and 2% by mass or less.

[0066] The thickness of the negative electrode active material layer 64 is not particularly limited, but is, for example, not less than 10 μm and not more than 300 μm, and preferably not less than 20 μm and not more than 200 μm.

[0067] The separator 70 may be a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, or polyamide. Such a porous sheet may have a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which a PP layer is laminated on both sides of a PE layer). A heat-resistant layer (HRL) may be provided on the surface of the separator 70.

[0068] The nonaqueous electrolyte 80 typically contains a nonaqueous solvent and a supporting salt (electrolyte salt). As the nonaqueous solvent, various organic solvents such as carbonates, ethers, esters, nitriles, sulfones, and lactones that are used in electrolytes of general lithium ion secondary batteries can be used without any particular limitation. Specific examples include ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), and trifluorodimethyl carbonate (TFDMC). Such nonaqueous solvents can be used alone or in appropriate combination of two or more.

[0069] As the supporting salt, for example, a lithium salt such as LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI) (preferably LiPF6) can be suitably used. The concentration of the supporting salt is preferably 0.7 mol / L or more and 1.3 mol / L or less.

[0070] The nonaqueous electrolyte 80 may contain various additives other than the above-mentioned components, such as film-forming agents such as vinylene carbonate (VC) and oxalate complexes; gas generating agents such as biphenyl (BP) and cyclohexylbenzene (CHB); and thickeners, as long as the effects of the present invention are not significantly impaired.

[0071] The lithium ion secondary battery 100 configured as described above is excellent in both capacity characteristics and output characteristics. That is, the lithium ion secondary battery 100 has a high capacity and a high output.

[0072] The lithium ion secondary battery 100 can be used for various purposes. Specific applications include portable power sources for personal computers, portable electronic devices, portable terminals, etc.; power sources for driving vehicles such as electric vehicles (BEVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs); and storage batteries for small power storage devices, among which a power source for driving vehicles is preferred. The lithium ion secondary battery 100 can also be used in the form of a battery pack typically consisting of a plurality of batteries connected in series and / or parallel.

[0073] As an example, a rectangular lithium ion secondary battery 100 including a flat wound electrode assembly 20 has been described. However, the lithium ion secondary battery disclosed herein can also be configured as a lithium ion secondary battery including a laminated electrode assembly (i.e., an electrode assembly in which multiple positive electrodes and multiple negative electrodes are alternately laminated). In addition, the nonaqueous electrolyte secondary battery disclosed herein can also be configured as a cylindrical lithium ion secondary battery, a laminated case type lithium ion secondary battery, a coin type lithium ion secondary battery, etc.

[0074] In addition, a secondary battery other than a lithium ion secondary battery can be constructed using the above-mentioned positive electrode according to a known method. Furthermore, an all-solid-state secondary battery (particularly an all-solid-state lithium ion secondary battery) can be constructed using a solid electrolyte instead of the nonaqueous electrolyte 80 according to a known method.

[0075] Examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.

[0076] <Examples 1 to 14 and Comparative Examples 1 to 5> As a precursor of the positive electrode active material, Ni 1 / 3 Co 1 / 3 Mn 1 / 3 A nickel-cobalt-manganese composite hydroxide represented by (OH)2 was prepared.

[0077] The first lithium composite oxide was produced by the following procedure. First, the prepared composite hydroxide and a lithium source (lithium carbonate) were mixed so as to have the Li / Me ratio shown in Tables 1 and 2. This was fired for 12 hours at the temperatures shown in Tables 1 and 2 to obtain the first lithium composite oxide (lithium nickel cobalt manganese composite oxide). In addition, in Examples 7, 13, and 14, a composite hydroxide having an average particle diameter (D50) of 7 μm was used, in Examples 9 and 10, a composite hydroxide having an average particle diameter (D50) of 3 μm was used, in Example 11, a composite hydroxide having an average particle diameter (D50) of 2 μm was used, in Example 12, a composite hydroxide having an average particle diameter (D50) of 11 μm was used, and in the other Examples and Comparative Examples, a composite hydroxide having an average particle diameter (D50) of 9 μm was used. Tables 1 and 2 show the average particle size (D50) of the first lithium composite oxide measured using a commercially available laser diffraction / scattering type particle size distribution measuring device.

[0078] The second lithium composite oxide was prepared by the following procedure. First, the composite hydroxide and the lithium source (lithium carbonate) were mixed to have the Li / Me ratio shown in Tables 1 and 2. This was baked for 12 hours at the temperature shown in Tables 1 and 2 to obtain the second lithium composite oxide (lithium nickel cobalt manganese composite oxide). In Example 8, a composite hydroxide having an average particle diameter (D50) of 7 μm was used, in Example 13, a composite hydroxide having an average particle diameter (D50) of 3 μm was used, in Example 14, a composite hydroxide having an average particle diameter (D50) of 11 μm was used, and in the other Examples and Comparative Examples, a composite hydroxide having an average particle diameter (D50) of 9 μm was used. The average particle diameter (D50) values ​​of the second lithium composite oxide measured using a commercially available laser diffraction / scattering type particle size distribution measuring device are shown in Tables 1 and 2.

[0079] The first and second lithium composite oxides thus prepared were mixed in the mass ratios shown in Tables 1 and 2 to obtain positive electrode active materials.

[0080] The obtained positive electrode active material, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVDF) as a binder were mixed in N-methylpyrrolidone (NMP) in a mass ratio of positive electrode active material:AB:PVDF=85:10:5 to prepare a paste for forming a positive electrode active material layer. This paste was applied onto an aluminum foil having a thickness of 15 μm and dried to prepare a positive electrode sheet.

[0081] A paste for forming a negative electrode active material layer was prepared by mixing natural graphite (C) as a negative electrode active material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener in ion-exchanged water in a mass ratio of C:SBR:CMC=98:1:1. This paste was applied to a copper foil with a thickness of 10 μm and dried to prepare a negative electrode sheet.

[0082] In addition, a porous polyolefin sheet having a thickness of 20 μm and a three-layer structure of PP / PE / PP was prepared as a separator sheet.

[0083] The positive electrode sheet, the negative electrode sheet, and the separator sheet were stacked, and the electrode terminals were attached to the laminate case, and the laminate case was housed. Next, a non-aqueous electrolyte was injected into the laminate case, and the laminate case was sealed airtight. The non-aqueous electrolyte was a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 3:4:3, and LiPF6 as a supporting salt was dissolved at a concentration of 1.0 mol / L. In this manner, lithium ion secondary batteries for evaluation of each example and each comparative example were obtained.

[0084] <Crystallite size measurement> The first lithium composite oxide and the second lithium composite oxide prepared above were analyzed using an XRD device "smart Lab" (manufactured by Rigaku) ​​and analysis software "PDXL2" (manufactured by Rigaku), and the crystallite size was calculated using the half-width and 2θ value of the diffraction peak (2θ=44±1°) assigned to the (004) plane and the Scherrer formula. The results are shown in Tables 1 and 2.

[0085] <Activation and initial capacity measurement> Each of the lithium ion secondary batteries for evaluation prepared above was placed in an environment of 25°C. Activation (initial charging) was performed using a constant current-constant voltage method, and each of the lithium ion secondary batteries for evaluation was charged at a constant current of 1 / 3C to 4.2V, and then charged at a constant voltage until the current value reached 1 / 50C, to be fully charged. Then, each of the lithium ion secondary batteries for evaluation was discharged at a constant current of 1 / 3C to 3.0V. The discharge capacity at this time was measured to determine the initial capacity. The ratio of the initial capacity of the other comparative examples and examples was determined when the initial capacity of Comparative Example 1 was taken as 1. The results are shown in Tables 1 and 2.

[0086] <Output characteristic evaluation> After activation treatment was performed on each evaluation lithium ion secondary battery, the SOC was adjusted to 60% and placed in an environment of -10°C. Each evaluation lithium ion secondary battery was discharged for 2 seconds at a current value of 15C. The output (W) was calculated based on the voltage and current value at this time. The output ratio of the evaluation lithium ion secondary battery using the positive electrode active material obtained in the other comparative examples and examples was calculated when the output of the evaluation lithium ion secondary battery using the positive electrode active material obtained in Comparative Example 1 was set to 1. The results are shown in Tables 1 and 2.

[0087] [Table 1]

[0088] [Table 2]

[0089] The results in Tables 1 and 2 show that when the Li / Me ratio in the first lithium composite oxide is 0.90 to 0.97, the Li / Me ratio in the second lithium composite oxide is 1.10 to 1.20, the crystallite diameter of the (104) plane of the first lithium composite oxide is 400 Å to 600 Å, and the crystallite diameter of the (104) plane of the second lithium composite oxide is larger than the crystallite diameter of the (104) plane of the first lithium composite oxide, both the capacity and output are high.

[0090] It is therefore evident that the positive electrode disclosed herein can impart high levels of both capacity and output characteristics to a secondary battery.

[0091] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the specific examples exemplified above.

[0092] That is, the positive electrode and secondary battery disclosed herein include the following items [1] to [6]. [1] A positive electrode comprising a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, the positive electrode active material layer contains a first lithium composite oxide having a layered structure and a second lithium composite oxide having a layered structure, In the first lithium composite oxide, a molar ratio of Li to metals other than Li is 0.90 to 0.97; In the second lithium composite oxide, a molar ratio of Li to metals other than Li is 1.10 to 1.20; The crystallite size of the (104) plane of the first lithium composite oxide is 400 Å to 600 Å, A positive electrode, wherein the crystallite size of the (104) plane of the second lithium composite oxide is larger than the crystallite size of the (104) plane of the first lithium composite oxide. [2] The crystallite size of the (104) plane of the second lithium composite oxide is 100 Å or more larger than the crystallite size of the (104) plane of the first lithium composite oxide; and Item [1]: The positive electrode according to item [1], wherein the second lithium composite oxide has a crystallite size of a (104) plane of 600 Å to 800 Å. [3] The positive electrode according to item [1] or [2], wherein the first lithium composite oxide and the second lithium composite oxide are both lithium nickel cobalt manganese-based composite oxides. [4] The positive electrode according to any one of items [1] to [3], wherein the first lithium composite oxide is recovered from a used lithium ion secondary battery. [5] The positive electrode according to any one of items [1] to [4], wherein the first lithium composite oxide has an average particle size (D50) of 3 μm to 8 μm. [6] The positive electrode according to any one of items [1] to [5], A negative electrode; An electrolyte; A secondary battery comprising: [Explanation of symbols]

[0093] 20 Wound electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 Positive electrode sheet (positive electrode) 52 Positive electrode current collector 52a Portion where positive electrode active material layer is not formed 54 Cathode active material layer 60 Negative electrode sheet (negative electrode) 62 Negative electrode current collector 62a Part where negative electrode active material layer is not formed 64 Negative electrode active material layer 70 Separator sheet (separator) 80 Non-aqueous electrolytes 100 Lithium-ion secondary battery

Claims

1. A positive electrode comprising a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, the positive electrode active material layer contains a first lithium composite oxide having a layered structure and a second lithium composite oxide having a layered structure, In the first lithium composite oxide, a molar ratio of Li to metals other than Li is 0.90 to 0.97; In the second lithium composite oxide, a molar ratio of Li to metals other than Li is 1.10 to 1.20; The crystallite size of the (104) plane of the first lithium composite oxide is 400 Å to 600 Å, a crystallite size of the (104) plane of the second lithium composite oxide is larger than a crystallite size of the (104) plane of the first lithium composite oxide.

2. The crystallite size of the (104) plane of the second lithium composite oxide is 100 Å or more larger than the crystallite size of the (104) plane of the first lithium composite oxide; and 2. The positive electrode according to claim 1, wherein the second lithium composite oxide has a crystallite size of a (104) plane of 600 Å to 800 Å.

3. 2. The positive electrode according to claim 1, wherein the first lithium composite oxide and the second lithium composite oxide are both lithium nickel cobalt manganese-based composite oxides.

4. 2. The positive electrode according to claim 1, wherein the first lithium composite oxide is recovered from a used lithium ion secondary battery.

5. The positive electrode according to claim 1, wherein the first lithium composite oxide has an average particle size (D50) of 3 μm to 8 μm.

6. The positive electrode according to claim 1 ; A negative electrode; An electrolyte; A secondary battery comprising:

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery, method for manufacturing the same, and lithium secondary battery including the same

    JP2012018925A

  • Positive electrode active material for nonaqueous electrolyte secondary batteries, manufacturing method thereof, and nonaqueous electrolyte secondary battery

    JP2015026454A

  • Positive electrode active material for non-aqueous electrolyte secondary battery

    JP2020030886A

  • Nickel-based composite positive electrode active material for lithium secondary battery, manufacturing method thereof, and lithium secondary battery including positive electrode including the same

    JP2022000846A

  • Method for regenerating positive electrode active material and positive electrode active material regenerated therefrom

    JP2024507559A